Pendampingan Pengelolaan Administrasi dan Fasilitas di Divisi General Affairs (GA) PT. Panorama Indah Permai - Riestiana Purwaji Putri; Riyono Riyono (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the role of the General Affairs (GA) Division in ensuring the effectiveness of administrative processes and facility management at PT. Panorama Indah Permai (Saloka Theme Park). The research was conducted during an internship program from September to December 2025, during which the researcher was directly involved in daily operational activities. Using a descriptive qualitative method, data were obtained through direct observation, administrative document analysis, and informal interviews with GA personnel. The results show that the GA Division functions as a critical support unit responsible for logistics management, documentation control, meeting room preparation, and operational vehicle administration. Several challenges were identified, including inconsistencies in documentation, high workload during peak operations, and limited digital integration. Despite these challenges, the GA Division plays a central role in coordinating with other departments to maintain workflow continuity. This study reinforces the relevance of operations management, office administration, facility management, and organizational communication theories in practical workplace settings. The findings imply that improving digital administrative systems, enhancing coordination mechanisms, and standardizing procedures could significantly strengthen GA performance and overall organizational efficiency.